A systematic quantitative review of the perceived environmental and natural resource-related impacts of unconventional oil and gas development. (December 2022) - Theodori, Gene L.; Wynveen, Brooklynn J.; Measham, Thomas; Evensen, Darrick
Highlights: Ninety-six journal articles on UOGD impacts were systematically reviewed. Majority of studies occurred in United States of America. In qualitative studies, water-related risks were expressed most by stakeholders. In quantitative studies, water-related risks were most-measured impact. Social science findings mirror those in environmental science literature. Abstract: In this paper, we present a systematic quantitative review of a sample of the international peer-reviewed human-subjects literature in which social science researchers incorporated environmental and natural resource-related variables into their scholarship on the local impacts of unconventional oil and gas development (UOGD). Specifically, this targeted review provides readers with an overview of the timing and geographic locations of studies on the perceived environmental/natural resource-related impacts of UOGD, as well as the methods used to collect the data from various types of human subjects. It also quantifies the perceived water-, air-, seismic-, and land-related impacts of UOGD as expressed by stakeholders in the qualitative studies or as measured by researchers in the studies that employed survey research techniques. The findings from this endeavor complement previously published review articles on the local impacts of UOGD and augment the natural resource social science literature on the topic.